Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/jmv.24551
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine effectiveness in preventing hospitalizations with laboratory-confirmed influenza in Greece during the 2014-2015 season: A test-negative study

Abstract: The 2014-2015 influenza season was marked by circulation of antigenically drifted A/H3N2 strains, raising the possibility of low seasonal influenza Vaccine Effectiveness (VE). We assessed VE against hospitalization with laboratory-confirmed influenza for the 2014-2015 season, using routine surveillance data. Non-sentinel swab samples from Greek hospital inpatients were tested for influenza by RT-PCR in three laboratories, covering the entire country. We estimated VE using a test-negative design. Out of 883 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Due to the limited number of TND studies reporting very severe outcomes, 45,52,88 we could not compute pooled IVE against ICU admission associated with laboratory confirmed influenza. Castilla et al 88 reported a higher IVE against ICU compared to hospitalized influenza and concluded that vaccination lowered the severity of hospitalized cases of influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited number of TND studies reporting very severe outcomes, 45,52,88 we could not compute pooled IVE against ICU admission associated with laboratory confirmed influenza. Castilla et al 88 reported a higher IVE against ICU compared to hospitalized influenza and concluded that vaccination lowered the severity of hospitalized cases of influenza.…”
Section: Discussionmentioning
confidence: 99%
“…We compared vaccination status in symptomatic adults who had PCR confirmed SARS-CoV-2 infection (case participants) with vaccination status in adults who reported symptoms of COVID-19 but had a negative PCR test for SARS-CoV-2 (control participants). Test negative case–control designs are considered powerful enough to estimate vaccine effectiveness and are used extensively for estimating effectiveness of influenza vaccines and vaccines against other respiratory viruses 14 15. They have been found to have high concordance with findings in randomised controlled trials 16…”
Section: Methodsmentioning
confidence: 99%
“…Influenza vaccination can offer substantial protection against hospitalization, even in years in which there is a degree of antigenic drift. 47 Hepatitis B virus Nosocomial transmission of hepatitis B virus has been documented since at least the early 1980s, 48,49 although the phenomenon was described more frequently and in ever more surprising forms in the 1990s. 50 Hepatitis B vaccines have not only resulted in global reductions in the burden of liver disease caused by hepatitis B virus, but also have conferred protection in the healthcare setting, especially for healthcare workers.…”
Section: Influenza Vaccinationmentioning
confidence: 99%
“…Influenza vaccination can offer substantial protection against hospitalization, even in years in which there is a degree of antigenic drift. 47…”
Section: Viral Infectionsmentioning
confidence: 99%